EVOLUTION OF INTERNATIONAL TRADE IN ROMANIA BETWEEN 2016 - 2018 WITH FORECASTS FOR 2019-2021 - RĂDESCU, Octavian Dan (Theoretical and Practical Research in Economic Fields; Vol 9 No 1 (2018): TPREF, Volume IX, Issue 1(17), Summer 2018, 2018)
In the introduction, the author focuses on a problem, in the past, present and future, eternal actually – globalization. Next, Romania's commercial policy is directed mainly towards the European Union, the largest economic bloc in Europe in 2017 compared to the 2016 or 2018 years, with forecasts for 2019-2021